2003
DOI: 10.1046/j.1471-4159.2003.01695.x
|View full text |Cite
|
Sign up to set email alerts
|

CAT2 arginine transporter deficiency significantly reduces iNOS‐mediated NO production in astrocytes

Abstract: We have previously demonstrated that genetic ablation of cationic amino acid transporter 2 (Cat2) significantly inhibits nitric oxide (NO) production by inducible nitric oxide synthase (iNOS) in activated macrophages. Here we report that iNOS activity is impaired by 84% in activated Cat2-deficient astrocytes. Cat2 ablation appears to reduce astrocyte NO synthesis by decreasing the uptake of the sole precursor, arginine, as well as by reducing the expression of iNOS following activation. Excessive or dysregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 39 publications
5
26
0
Order By: Relevance
“…In line with findings of other investigators (53,71,72), our studies showed that inhibition of NOS2 and of IFN-␥ signaling abrogated the suppressive effect of P. gingivalis-induced MDSC on CD4 ϩ T cell proliferation. These observations indirectly suggest that secretion of NO requires surface and soluble signals, such as NOS2 and IFN-␥ from activated T cells, factors that contribute to immune suppression.…”
Section: Discussionsupporting
confidence: 92%
“…In line with findings of other investigators (53,71,72), our studies showed that inhibition of NOS2 and of IFN-␥ signaling abrogated the suppressive effect of P. gingivalis-induced MDSC on CD4 ϩ T cell proliferation. These observations indirectly suggest that secretion of NO requires surface and soluble signals, such as NOS2 and IFN-␥ from activated T cells, factors that contribute to immune suppression.…”
Section: Discussionsupporting
confidence: 92%
“…1, A and B). These results showed that the release of NO was significantly reduced in either peritoneal or airway macrophages in the absence of the CAT-2 gene, as is consistent with what has been previously reported (26).…”
Section: Resultssupporting
confidence: 93%
“…However, the background of KO animals (C57BL/6 or BALB/c) does not explain these discrepancies because similar results were found when we used the two strains (data not shown). It should be noted that for these authors, the production of NO in fibroblasts and astrocytes is not completely dependent on CAT2 (35,36).…”
Section: Discussionmentioning
confidence: 79%